Relevance of obesity-related organ damage and metabolic syndrome classification in cardiovascular and renal risk stratification in patients with essential hypertension - Petramala, Luigi; Gigante, Antonietta; Sarlo, Francesca; Servello, Adriana; Circosta, Francesco; Marino, Luca; Ciccarelli, Antonello; Cavallaro, Giuseppe; Letizia, Claudio (Frontiers in Cardiovascular Medicine, 2024)
Introduction: Hypertension is relevant cardiovascular comorbidity. Adipose tissue represents a metabolically active tissue involved in the regulation of blood pressure and metabolic alterations. In recent decades several classifications for the Metabolic Syndrome (MS) have been proposed. Recently, a new syndrome called "Cardiovascular-kidney-metabolic" was identified, in order to identify patients at high cardiovascular and metabolic risk; the aim of the study was to compare different classifications in a large population of hypertensive patients. Materials and methods: Between September 2022 and August 2023, we have consecutively enrolled 772 hypertensive patients (407M; 365W; mean age 52.2±15.1yrs), evaluating anthropometrics, biochemical and instrumental parameters (transthoracic echocardiogram, carotid echo-Doppler, 24-h ambulatory blood pressure monitoring, fundus oculi). Results: Using different classifications we have found MS prevalence: ATP-III 28.8%, IDF 31.5%, CKM 40.7%. CKM Class 3 and 4 showed higher BMI and waist circumference with respect to other groups. Compared to ATP-III and IDF, CKM Class 4 showed higher 24-hrs systolic blood pressure, lower percentage of controlled hypertension, increased interventricular septum and posterior wall, reduced ejection fraction and greater prevalence of hypertensive arterial retinal damage. Discussion: visceral obesity and MS are frequent conditions with healthy impact, becoming an important trigger for the development of cardiovascular and metabolic complications. The different MS classifications allow the early identification of patients at high risk of cardiometabolic complications. The new CKM syndrome proves useful to identify individuals at high risk for CKM morbidity and mortality.